Second TURB, restaging TURB or repeat TURB in primary T1 non-muscle invasive bladder cancer: impact on prognosis - Beijert, Irene J; Hentschel, Anouk E; Bründl, Johannes; Compérat, Eva M; Plass, Karin; Rodríguez, Oscar; Subiela Henríquez, Jose D; Hernández, Virginia; de la Peña, Enrique; Alemany, Isabel; Turturica, Diana; Pisano, Francesca; et al. (International urology and nephrology, 2024)
PURPOSE: A re-transurethral resection of the bladder (re-TURB) is a well-established approach in managing non-muscle invasive bladder cancer (NMIBC) for various reasons: repeat-TURB is recommended for a macroscopically incomplete initial resection, restaging-TURB is required if the first resection was macroscopically complete but contained no detrusor muscle (DM) and second-TURB is advised for all completely resected T1-tumors with DM in the resection specimen. This study assessed the long-term outcomes after repeat-, second-, and restaging-TURB in T1-NMIBC patients. METHODS: Individual patient data with tumor characteristics of 1660 primary T1-patients (muscle-invasion at re-TURB omitted) diagnosed from 1990 to 2018 in 17 hospitals were analyzed. Time to recurrence, progression, death due to bladder cancer (BC), and all causes (OS) were visualized with cumulative incidence functions and analyzed by log-rank tests and multivariable Cox-regression models stratified by institution. RESULTS: Median follow-up was 45.3 (IQR 22.7-81.1) months. There were no differences in time to recurrence, progression, or OS between patients undergoing restaging (135 patients), second (644 patients), or repeat-TURB (84 patients), nor between patients who did or who did not undergo second or restaging-TURB. However, patients who underwent repeat-TURB had a shorter time to BC death compared to those who had second- or restaging-TURB (multivariable HR 3.58, P = 0.004). CONCLUSION: Prognosis did not significantly differ between patients who underwent restaging- or second-TURB. However, a worse prognosis in terms of death due to bladder cancer was found in patients who underwent repeat-TURB compared to second-TURB and restaging-TURB, highlighting the importance of separately evaluating different indications for re-TURB.
Keywords: Neoplasm Staging; prognóza; cystektomie; Non-Muscle Invasive Bladder Neoplasms; Prognosis; Urologic Surgical Procedures; lidé; Cystectomy; staging nádorů; Urinary Bladder Neoplasms; Urinary Bladder; urologické chirurgické výkony; nádory močového měchýře; močový měchýř; nádory močového měchýře neinvadující svalovinu; Humans